2018
DOI: 10.1002/art.40356
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Antibody Repertoire in Neuropsychiatric Systemic Lupus Erythematosus and Neuromyelitis Optica Spectrum Disorder

Abstract: Patients with demyelinating NPSLE should be tested for IgG antibodies to AQP-4, MOG, and DWEYS. IgG anti-AQP-4 can be considered diagnostic for NMOSD, whereas none of these antibodies appear to be diagnostic for demyelinating NPSLE. Moreover, IgG anti-dsDNA are present in patients with NMOSD but are not cross-reactive with IgG anti-DWEYS, indicating that the antigenic stimulus and mechanisms of tissue damage are potentially different between demyelinating NPSLE and NMOSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 39 publications
(57 reference statements)
0
46
0
3
Order By: Relevance
“…A recent study investigated the frequency of autoantibodies classically associated with neuropsychiatric SLE (NPSLE), like ANA and anti-dsDNA, in patients with NMOSD [ 31 ]. Eighty-eight percent of patients with coexisting NMOSD had AQP4-IgG in the serum, whereas AQP4-IgG was only present in the serum of three percent of patients with NPSLE alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study investigated the frequency of autoantibodies classically associated with neuropsychiatric SLE (NPSLE), like ANA and anti-dsDNA, in patients with NMOSD [ 31 ]. Eighty-eight percent of patients with coexisting NMOSD had AQP4-IgG in the serum, whereas AQP4-IgG was only present in the serum of three percent of patients with NPSLE alone.…”
Section: Discussionmentioning
confidence: 99%
“…Eighty-eight percent of patients with coexisting NMOSD had AQP4-IgG in the serum, whereas AQP4-IgG was only present in the serum of three percent of patients with NPSLE alone. In addition, no AQP4-IgG's were found in SLE patients without neuropsychiatric symptoms [ 31 ]. MOG-IgG antibodies were only detected in patients with NMOSD who were negative for AQP4-IgG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-DNA/NR2 levels in PSNP-SLE were similar with de novo NPSLE, indicating that PSNP-SLE shares some of the clinical features of NPSLE as we suggested in the previous report (10). Mader et al reported the titers of anti-DNA/NR2 antibodies in NPSLE and SLE without NP manifestations (19), indicating that high titer of anti-DNA/NR2 antibodies may be predictive of NPSLE developing.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, it was demonstrated that a subset of murine anti-DNA antibodies cross-reacted with a sequence within the N-methyl-D-aspartate (NMDA) receptor subunit NR2 5 6. More importantly, recent studies have demonstrated that CSF anti-NMDA receptor NR2 antibodies (anti-NR2) are associated with diffuse psychiatric/neuropsychological syndromes of human NPSLE 7–9…”
Section: Introductionmentioning
confidence: 99%